Enhancing cycle life and usable energy density of fast charging LiFePO4-graphite cell by regulating electrodes’ lithium level - Vallabha Rao Rikka; Sumit Ranjan Sahu; Abhijit Chatterjee; Raju Prakash; G. Sundararajan; R. Gopalan (iScience, 2022)
Summary: Range anxiety is a primary concern among present-day electric vehicle (EV) owners, which could be curtailed by maximizing the driving range per charge or reducing the charging time of the lithium-ion battery (LIB) pack. Maximizing the driving range is a multifaceted task as charging-discharging the LIB up to 100% of its nominal capacity is limited by the cell chemistry (voltage window) and cell operating conditions. Our studies on commercial LiFePO4/graphite cells show that a cycle life of 4320 is achieved at 4C rate with 80% SOC-100% DOD combination (12 min charging time), which is the highest among the works reported with this cell chemistry. Complete utilization of electrodes’ lithium during cycling resulted in the lowest cycle life of 956. This study demonstrates LIB charging-discharging protocol enabling longer driving range with quicker charging times. Besides, it might endow promising possibilities of future EV LIB packs with reduced size/weight and high safety.